Analysis Of Decision Support Systems for Candidate Selection Scholarship Recipients Using TOPSIS Method - Asrul, Sani; Siti, Aisyah; Reida, Rachmawati; Dian, Ikha P; Ninuk, Wiliani (2022)
The high cost of completing education is one of the problems that exist in Indonesia. In order to solve this issue, one of the things that can be done is to provide scholarship assistance to students who excel or are less able. In every educational institution, especially in high school (SMA), there are many scholarships offered to students who excel and less fortunate students. With so many students who want to get these scholarships, a decision support system is needed to receive scholarships as expected. The current manual system can be inaccurate, considering that several criteria must be carefully considered. The average value of report cards, behavior, attendance, the amount of parental income, and the number of dependents of parents are all criteria that must be considered when evaluating prospective scholarship recipients. This study uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to select scholarship recipients. The objectives of this study are how to develop a Decision Support System model with the TOPSIS methods for determining exemplary student for scholarship.